A multicreteria perspective on reverse auctions - De Smet, Yves (Universite Libre de Bruxelles, 2005)
Investigate the use of partial relations for multicriteria reverse auctions. At first, a theoretical framework is introduced. Then, an extension of traditional multicriteria tools is considered. This is referred to as the Butterfly model. Finally, the concept of Bidding Niches partitions is formalized and tested. === Doctorat en sciences appliquées === info:eu-repo/semantics/nonPublished